Risk assessment in equine anesthesia: a first evaluation of the usability, utility and predictivity of the two-part CHARIOT - Brumund, Lisa; Wittenberg-Voges, Liza; Rohn, Karl; Kästner, Sabine B. R. (Frontiers in Veterinary Science, 2024)
An accurate risk score that can predict peri-anesthetic morbidity and mortality in equine patients could improve peri-operative management, outcome and client communication. Therefore, 300 horses underwent pre-anesthetic risk assessment using the American Society of Anesthesiologists-Physical Status augmented with equine-specific diseases (ASA-PS-Equine), a multifactorial 10-part rubric risk scale (10-RS), and a combination of both, the Combined horse anesthetic risk identification and optimization tool (CHARIOT). Intra- and post-anesthetic complications, the recovery phase and mortality were recorded over a period of seven days following general anesthesia. To compare the utility and predictive power of the 3 scores, data were analyzed using binominal logistic regression (p ≤ 0.05) and receiver operating characteristic curve analysis. In addition, inter-observer reliability, speed, safety, ease of use and face validity of the ASA-PS-Equine and the 10-RS were analyzed based on five hypothetical patients. All scores showed statistically significant associations with various intra-anesthetic complications and parameters of the recovery phase. The discriminant ability of the scores related to the occurrence of intra-anesthetic (AUC = 0.6093-0.6701) and post-anesthetic (AUC = 0.5373-0.6194) complications was only low. The highest diagnostic accuracy for all scores was observed for overall mortality (AUC = 0.7526-0.7970), with the ASA-PS-Equine differentiating most precisely (AUC = 0.7970; 95% CI 0.7199-0.8741). Inter-observer reliability was fair for the 10-RS (κ = 0.39) and moderate for the ASA-PS-Equine (κ = 0.52). Patient assignment to the CHARIOT was predominantly rated as rather easy and quick or very quick. The main limitations of the study are the monocentric study design and failure to obtain the full range of points. In conclusion, all 3 scores provide useful information for predicting the mortality risk of equine patients undergoing general anesthesia, whereas intra- and postoperative complications cannot be predicted with these scores.